Maximal Regularity for Time-Stepping Schemes Arising from Convolution Quadrature of Non-Local in Time Equations - Lizama-Yanez, C (American Institute of Mathematical Sciences, 2022)
We study discrete time maximal regularity in Lebesgue spaces of sequences for time-stepping schemes arising from Lubich s convolution quadrature method. We show minimal properties on the quadrature weights that determines a wide class of implicit schemes. For an appropriate choice of the weights, we are able to identify the θ-method as well as the backward differentiation formulas and the L1-scheme. Fractional versions of these schemes, some of them completely new, are also shown, as well as their representation by means of the Grünwald-Letnikov fractional order derivative. Our results extend and improve some recent results on the subject and provide new insights on the basic nature of the weights that ensure maximal regularity. © 2022 American Institute of Mathematical Sciences. All rights reserved.